8+2(8x-6)=16x+4

Simple and best practice solution for 8+2(8x-6)=16x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8+2(8x-6)=16x+4 equation:


Simplifying
8 + 2(8x + -6) = 16x + 4

Reorder the terms:
8 + 2(-6 + 8x) = 16x + 4
8 + (-6 * 2 + 8x * 2) = 16x + 4
8 + (-12 + 16x) = 16x + 4

Combine like terms: 8 + -12 = -4
-4 + 16x = 16x + 4

Reorder the terms:
-4 + 16x = 4 + 16x

Add '-16x' to each side of the equation.
-4 + 16x + -16x = 4 + 16x + -16x

Combine like terms: 16x + -16x = 0
-4 + 0 = 4 + 16x + -16x
-4 = 4 + 16x + -16x

Combine like terms: 16x + -16x = 0
-4 = 4 + 0
-4 = 4

Solving
-4 = 4

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| Xy+xz=1 | | f(x)=2x^2+12 | | 3x+32=56 | | 5(b+3)=3b+23 | | 3x-8=56 | | 4x+9-2x+2=3x-5-x | | 12-6x=2x+10 | | 11x+32=56 | | 3x-4=-x+6 | | U=5(6n+31)+9(n+1) | | 7x-2=3x-22 | | 40x+70y=6000 | | 3w+4=5m+7-m | | X+3x+2y= | | 2(3-x)+7=2x-(x-4) | | 6x+12=12x+6 | | 0.5x+1=2.5x | | 4y-5x=60 | | 8z=2xb | | 12=2(x-4)-6 | | 2(3-x)+7=2x-4(x-4) | | 3(h+4)+5=35 | | (1+x)(1+z)= | | 10x^2+1210=0 | | 2ydx-2xdy=0 | | 18i-14i= | | 5x+-6+2=7x+-6 | | .6k-(k+.25)=.05(k+1) | | Z-4z=9z-9-z | | 2(5-2v)=5(v-5) | | 87-n=13 | | 24n^3+30n^2=0 |

Equations solver categories